2008
DOI: 10.1177/1934578x0800301234
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Gastroprotective and Antiulcer Agents: Recent Developments

Abstract: Peptic ulcer, one of the most common gastrointestinal diseases, is a chronic inflammatory disease characterized by ulceration in the regions of the upper gastrointestinal tract where parietal cells are found and where they secrete hydrochloric acid and pepsin. The anatomical sites where ulcer occurs commonly are stomach and duodenum, causing gastric and duodenal ulcer, respectively. Physiopathology of ulcer is due to an imbalance between aggressive factors, such as acid, pepsin, Helicobacter pylori and non-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…Medicinal plants that are traditionally used to treat ulcers are one of the most attractive sources of natural products as gastroprotective agents. [18][19][20][21][22] The gastroprotective activity of terpenes of various skeletal types under different experimental conditions has been reported in the literature but showed significant activity only at a single oral dose of 100 mg/kg. [19][20][21][22][23] In a previous study, we found a gastroprotective effect of some of the ferruginol derivatives tested that was comparable with the Azorella diterpenoids reported here under the same experimental conditions (20 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants that are traditionally used to treat ulcers are one of the most attractive sources of natural products as gastroprotective agents. [18][19][20][21][22] The gastroprotective activity of terpenes of various skeletal types under different experimental conditions has been reported in the literature but showed significant activity only at a single oral dose of 100 mg/kg. [19][20][21][22][23] In a previous study, we found a gastroprotective effect of some of the ferruginol derivatives tested that was comparable with the Azorella diterpenoids reported here under the same experimental conditions (20 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] The gastroprotective activity of terpenes of various skeletal types under different experimental conditions has been reported in the literature but showed significant activity only at a single oral dose of 100 mg/kg. [19][20][21][22][23] In a previous study, we found a gastroprotective effect of some of the ferruginol derivatives tested that was comparable with the Azorella diterpenoids reported here under the same experimental conditions (20 mg/kg). [24] However, in comparison with poligodial, carnosol, 6,7-royleanone, 7,20epoxiroyleanone, royleanone and horminone, under the same the conditions, the gastroprotective effect of Azorella diterpenes is lower.…”
Section: Discussionmentioning
confidence: 99%
“…Many plants have been used in traditional medicine to treat different diseases, including gastrointestinal disorders. Among the naturally-occurring compounds in plants, terpenes or their derivatives have been shown to possess gastroprotective activity in different models of gastric lesions in animals [1,2]. Recently, two plastoquinones and a chromene from the brown alga Sargassum micracanthum were shown to display antiulcer effects on HCl/EtOH induced gastric lesions [3].…”
mentioning
confidence: 99%
“…Although in most cases the origin of gastric ulcer is unknown, it is generally accepted that it is the result of an imbalance between defensive and aggressive factors in the gastric mucosa [2,9]. Oral administration of the HCl/ethanol solution to mice clearly produced multiple hemorrhagic lesions in the glandular portion of the stomach.…”
mentioning
confidence: 99%
See 1 more Smart Citation